Post-traumatic stress disorder in patients with systemic lupus erythematosus heavily affects quality of life. A cross-sectional web survey-based study. (February 2023) - Moroni, Luca; Mazzetti, Martina; Ramirez, Giuseppe Alvise; Zuffada, Simone; Ciancio, Anna; Gallina, Gabriele; Farina, Nicola; Bozzolo, Enrica; Di Mattei, Valentina; Dagna, Lorenzo
Objectives: Neuropsychiatric symptoms develop in up to 20% of the patients with Systemic Lupus Erythematosus (SLE). Growing evidence is accruing on the association of SLE with Post-traumatic Stress Disorder (PTSD), but little is known about its contribution on patient-reported outcomes. This study focuses on PTSD prevalence in our SLE cohort and on its impact on quality of life. Methods: Trauma and Loss Spectrum – Self Reported (TALS-SR) and Lupus Quality of Life (Lupus QoL) questionnaires were administered via web to the patients with SLE in our cohort, along with questions on demographical and disease-related aspects. Results: Among 99 patients who completed the questionnaire, fatigue prevalence was 75% and 31% scored TALS-SR test consistently with PTSD. Patients with PTSD achieved lower scores compared to those without PTSD in three Lupus QoL domains: planning (83.3 vs. 100, p = .035), body image (85.0 vs. 95.0, p = .031) and fatigue (66.7 vs. 91.7, p = .001). An inverse correlation was found between TALS-SR domains and Lupus QoL scores, particularly regarding fatigue with reaction to losses or upsetting events (ρ -0.458, p < .001). Conclusions: PTSD is possibly far more frequent in patients with SLE than in general population and exerts a detrimental influence on quality of life.